2022
DOI: 10.1007/s10354-022-00988-1
|View full text |Cite
|
Sign up to set email alerts
|

Onychomadesis in a COVID-19 patient

Abstract: We report the case of a 67-year-old woman who developed onychomadesis on 9 of her fingers 2 months after recovering from COVID-19, with subsequent full nail regrowth after 4 months. The development of onychomadesis in COVID-19 is probably related to inhibition of nail proliferation due to fever, direct viral damage, or an inflammatory process associated with endothelial damage and obliterative microangiopathy in the nail matrix area. Clinicians should be aware of nail changes and actively seek them out in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Nevertheless, as far as we know, the chance is relatively low in ordinary situations. Unless apparent systemic, infectious, or neoplastic nail disorders or direct trauma are found, a surgeon can consider some circumstances affecting the microcirculation of the fingertip, which lead to nail plate disorders [5,[8][9][10]. Recently, some reports showed that nail change is related to coronavirus disease 2019; however, there were no infections, especially viral, in this case [8].…”
Section: Discussionmentioning
confidence: 73%
“…Nevertheless, as far as we know, the chance is relatively low in ordinary situations. Unless apparent systemic, infectious, or neoplastic nail disorders or direct trauma are found, a surgeon can consider some circumstances affecting the microcirculation of the fingertip, which lead to nail plate disorders [5,[8][9][10]. Recently, some reports showed that nail change is related to coronavirus disease 2019; however, there were no infections, especially viral, in this case [8].…”
Section: Discussionmentioning
confidence: 73%
“…These are rare changes that occur in patients of all ages, regardless of their origin [104,105]. As a result of infection with the SARS-CoV-2 virus, the following have been reported: the following changes on the nails: a red crescent sign, Mees' lines, Beau's lines [106][107][108]. The red crescent sign is the most common post-COVID-19 change that affects the nails.…”
Section: Nail Changesmentioning
confidence: 99%
“…A raised erythematous line over the distal end of the lunula is described [ 104 , 108 ]. This symptom usually occurs 2–3 weeks after the SARS-CoV infection and disappears spontaneously within 2–3 months [ 106 , 108 , 109 ]. The red crescent symptom was also reported two days after the onset of symptoms of the SARS-CoV-2 infection [ 107 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though most cases are idiopathic, it can also occur secondary to infections like hand, foot and mouth disease (HFMD), inflammatory conditions like erythroderma and Kawasaki disease, and autoimmune conditions like Pemphigus vulgaris, alopecia areata or drug-induced cases, especially with chemotherapy agents, antiepileptics, azithromycin and retinoids 1–5. Rarely, onychomadesis can be associated with depression, zinc deficiency, cast immobilisation, COVID-19 infection and birth trauma 2 6 7. The median onset of nail shedding is approximately 40 days following HFMD.…”
Section: Descriptionmentioning
confidence: 99%